2022
DOI: 10.1016/j.gocm.2022.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high salt-diet increases offspring's blood pressure with dysfunction of NO/PKGI signaling pathway in heart tissue

Abstract: BackgroundHigh salt-diets have become significant threats to human health, resulting in hypertension and cardiovascular diseases. Hypertensive disorders during pregnancy are complicated, since the maternal cardiovascular system undergoes extensive physiological changes during pregnancy. High-salt diets during pregnancy can disturb the intrauterine environment and negatively affect fetal development. Therefore, we explored how high-salt diets during pregnancy could affect the offspring.MethodsRats were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…42 Conversely, the Ca 2+ level in ISF was reduced by HSD and completely recovered by subsequent LSD. This is because hypernatremia causes hypertension 43 and excretion of excess sodium ions through the kidney, which in turn causes the loss of Ca 2+ ions. 44 Previous studies in humans have shown that every 0.6 mM increase in ISF K + reduces pH by ∼0.1 unit.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…42 Conversely, the Ca 2+ level in ISF was reduced by HSD and completely recovered by subsequent LSD. This is because hypernatremia causes hypertension 43 and excretion of excess sodium ions through the kidney, which in turn causes the loss of Ca 2+ ions. 44 Previous studies in humans have shown that every 0.6 mM increase in ISF K + reduces pH by ∼0.1 unit.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In experimental studies, high salt intake affects health negatively and increases body weight, blood insulin and glucose levels namely metabolic syndrome in rats (8). Excessive salt intake during the fetal period may adversely affect the fetus (9). High salt intake during pregnancy and lactation may also exacerbate the detrimental impact of the Western diet on the offspring (2).…”
Section: Introductionmentioning
confidence: 99%